Investigating how to achieve an Islamic state in the Islamic world - DADI, REZA ALLAH; DEHNAVI, MOHSEN HOSSEINI; BAYATI, HADI (The journal of contemporary issues in business and government, 2021)
There has been a lot of theoretical discussion about how to achieve an Islamic state, and some Shiite movements have been formed to achieve it, but there was no news of it in practice. Ayatollah Khamenei, with his unparalleled efforts, has provided solutions for the formation of the Islamic State, while clarifying how the legitimacy of the Islamic State is and proving that the truth of religion is impossible except with the implementation of a religious government. Accordingly, this research, with a descriptive-analytical method and relying on the statements of Ayatollah Khamenei, seeks to examine how to achieve an Islamic state from His Holiness's point of view. Findings indicate that considering the current situation of Muslim societies that are planning and shaping the Islamic state and despite the forward movement of Islamic civilization, always provide obstacles to the formation of the Islamic state. Therefore, Ayatollah Khamenei considers the grounds for achieving an Islamic state to be attention to monotheism, pivotal governance, resistance, the existence of leadership, the production of thought, and economic advancement.